Edukasi pengetahuan masyarakat dalam pemanfaatan daun insulin di Desa Jambi Kecil Kabupaten Muaro Jambi - Brata, Andy; Sugiarti, Sugiarti (Jurnal Pengabdian Harapan Ibu (JPHI), 2023)
The insulin plant (Tithonia diversifolia (Hemsl.) A. Gray) is a flowering plant with orange-colored flowers that belongs to the Asteraceae family. It can be cultivated as an ornamental plant in gardens or green spaces and used in traditional medicine. The benefits and potential of this plant are numerous, including its use as green manure, pest, and disease control, fodder for livestock, soil and water conservation, and its potential in traditional treatments for urinary tract infections, digestive issues, and diabetes management. This community service aims to enhance public knowledge regarding using insulin plant leaves as crude drugs for diabetes treatment. The method employed involves conducting informational sessions through lectures followed by a question-and-answer session. The results show the community learned about using insulin plants as a diabetes remedy. The community's knowledge about using insulin plants as a traditional remedy as a decoction for diabetes treatment increased to 100%.